Striking a Balance : Managing El Niño and La Niña in Cambodia’s Agriculture - Sutton, William R. (World Bank, Washington, DC, 2019)
The purpose of this report is to help Cambodia’s policy makers and stakeholders prepare for future El Niño–Southern Oscillation (ENSO) events. It does this by providing information on ENSO’s poverty, economic, and agricultural impacts in Cambodia and outlining ways forward. The report finds that ENSO’s impacts vary from region to region and harm Cambodia’s people, economy, and agricultural sector. The country has made inroads in preparing for climate events like floods and other natural disasters, but more could be done to prepare for ENSO specifically. Being proactive to prepare for ENSO in Cambodia is important because of the country’s high exposure to climate shocks, the prominence of the agricultural sector in the national economy, the large rural population and its climate vulnerability.